Impaired Cuticle Functionality and Robust Resistance to Botrytis cinerea in Arabidopsis thaliana Plants With Altered Homogalacturonan Integrity Are Dependent on the Class III Peroxidase AtPRX71 - Lorrai, Riccardo; Francocci, Fedra; Gully, Kay; Martens, Helle J.; De Lorenzo, Giulia; Nawrath, Christiane; Ferrari, Simone (Frontiers in Plant Science, 2021)
Pectin is a major cell wall component that plays important roles in plant development and response to environmental stresses. Arabidopsis thaliana plants expressing a fungal polygalacturonase (PG plants) that degrades homogalacturonan (HG), a major pectin component, as well as loss-of-function mutants for QUASIMODO2 (QUA2), encoding a putative pectin methyltransferase important for HG biosynthesis, show accumulation of reactive oxygen species (ROS), reduced growth and almost complete resistance to the fungal pathogen Botrytis cinerea. Both PG and qua2 plants show increased expression of the class III peroxidase AtPRX71 that contributes to their elevated ROS levels and reduced growth. In this work we show that leaves of PG and qua2 plants display greatly increased cuticle permeability. Both increased cuticle permeability and resistance to B. cinerea in qua2 are suppressed by loss of AtPRX71. Increased cuticle permeability in qua2, rather than on defects in cuticle ultrastructure or cutin composition, appears to be dependent on reduced epidermal cell adhesion, which is exacerbated by AtPRX71 and is suppressed by the esmeralda1 mutation, which also reverts the adhesion defect and the resistant phenotype. Increased cuticle permeability, accumulation of ROS and resistance to B. cinerea are also observed in mutants lacking a functional FERONIA, a receptor-like kinase thought to monitor pectin integrity. In contrast, mutants with defects in other structural components of primary cell wall do not have a defective cuticle and are normally susceptible to the fungus. Our results suggest that disrupted cuticle integrity, mediated by peroxidase-dependent ROS accumulation, plays a major role in the robust resistance to B. cinerea of plants with altered HG integrity.